Quality of Life Questionnaire-Bronchiectasis: a study of the psychometric properties of the Brazilian Portuguese version. (July 2020) - de Camargo, Cristiane O; José, Anderson; Luppo, Adriano; de Camargo, Anderson A; Athanazio, Rodrigo A; Rached, Samia Z; Quittner, Alexandra L; Stelmach, Rafael; Dal Corso, Simone
Objective: To evaluate the psychometric properties of the Brazilian Portuguese version of the Quality of Life Questionnaire-Bronchiectasis. Design: Cross-sectional study. Setting: Outpatient clinic. Subjects: Clinically stable individuals with a diagnosis of bronchiectasis. Measures: The evaluations performed were spirometry, incremental shuttle walk test, Saint George's Respiratory Questionnaire, and the modified Medical Research Council dyspnea scale. The Quality of Life Questionnaire-Bronchiectasis was administered twice (seven to 14 days apart). Psychometric analyses were performed as follows: reliability, construct validity, criterion validity, and interpretability. Results: In total, 108 individuals (48 ± 14 years, 61 women) participated in the study. Internal consistency was considered adequate (Cronbach's alpha ⩾ 0.70) for the majority of scales (from 0.58 to 0.93). Test–retest coefficients were moderate to excellent (intraclass correlation coefficients from 0.70 to 0.93). In the construct validity, 35 of 37 items correlated more strongly with their assigned scale than a competing scale. The convergent validity showed significant correlations between scales of the Quality of Life Questionnaire-Bronchiectasis with modified Medical Research Council dyspnea scale, and incremental shuttle walk test (r from 0.20 to 0.59). A low to moderate correlations was revealed between all scales of the Quality of Life Questionnaire-Bronchiectasis and the Saint George's Respiratory Questionnaire domains (r from 0.26 to 0.70). The standard error of measurement was acceptable. Ceiling effects were found for the Social Functioning and Treatment Burden scales. Conclusions: The Quality of Life Questionnaire-Bronchiectasis is a reliable, valid instrument with adequate internal consistency for the evaluation of the impact of bronchiectasis on the health-related quality of life of Brazilian adults.